Pemikiran Ahmad Mustafa al-Maraghi dalam tafsir al-Maraghi dan pengaruhnya terhadap pengajian tafsir di Malaysia / Amiratul Munirah Yahaya - Amiratul Munirah , Yahaya (2015)
This research examines the thoughts of Ahmad Mustafa al-Maraghi (1883-1952) in Tafsir al-Maraghi and his influence towards Quranic exegesis in Malaysia. The book of Tafsir al-Maraghi, with modern approach of Quranic exegesis, encompasses of Abduh’s thoughts using al-Adabi wa al-Ijtima'i method which links the interpretation of the meanings of Quranic verses with the social-cultural issues in the society. Through al-Maraghi’s writing, the ‘Kaum Muda’ of the mid-20th century widespread the reformist thoughts of al-Maraghi who teachers were Shaykh Muhammad 'Abduh and Sayyid Muhammad Rashid Rida. The research objectives are to present the biography of al-Maraghi, introduce his book Tafsir al-Maraghi, clarify his thoughts in the book from faith, political, social and economy, and examine the influence of al-Maraghi’s tafsir through Quranic studies in Malaysia. The study of the influence of al-Maraghi’s thoughts by teaching and Malay’s tafsir writings through his book, Tafsir al-Maraghi was theorized based on the Theory of Diffusion of Innovation by Barbara Wejnert (2002). The duration of study of the influence on teaching in Malaysia was between 1945-1965. Data collection of this qualitative research was done through library research, documentation analysis and semi-structured interview. The data analysis methods used were inductive, deductive and comparative methods with the application of descriptive statistics. The finding of the research shows that the teaching of the Quranic exegesis using Tafsir al-Maraghi between 1945-1965 occurred in Kelantan, Perak and Melaka. The ‘Kaum Muda’ popularized reformist method of interpretation of Quranic verses. In fact the tafsir book was used in the syllabus of tafsir subject at Arabic secondary schools, and became the main reference in tafsir writings written in the Malay Languages until today in Malaysia which indirectly outspread the thoughts of al-Maraghi’s.